Thyme Essential Oil Reduces Disease Severity and Induces Resistance against Alternaria linariae in Tomato Plants - Luis Alberto Saltos-Rezabala; Patrícia Ricardino Da Silveira; Dérica Gonçalves Tavares; Silvino Intra Moreira; Thiago Alves Magalhães; Deila Magna Dos Santos Botelho; Eduardo Alves (Horticulturae, 2022)
Currently, the use of alternative tools for chemical control has become one of the most sustainable and eco-friendly options for crop protection against phytopathogens. Thus, the present study aimed to assess the effect of essential oils (EOs) on the control of tomato early blight (EB), a highly destructive disease of this crop. The antifungal activity and ability to induce resistance induction of the EOs of thyme (Thymus vulgaris), lemongrass (Cymbopogon citratus) and tea tree (Melaleuca alternifolia) were tested for control of A. linariae in tomato plants. In vitro, mycelial growth and conidial germination were strongly inhibited when thyme EO (TEO; 2000 ppm) and lemongrass (LGEO; 2000 ppm) were applied. The infected leaf area and final disease index were decreased by 47.78% and 39.00%, respectively, compared to the water treatment. Foliar spraying with TEO increased the activity of the defense-related enzymes peroxidase, polyphenol oxidase and β-1,3-glucanase. Furthermore, callose deposition and phenolic compound accumulation in tissues infected by A. linariae improved after TEO application. In conclusion, TEO stimulated the defense system of tomato plants infected by A. linariae, which was associated with a reduced severity of EB. These results indicate that TEO is a potential tool in tomato EB disease management.